Emerging roles of Abl family tyrosine kinases in microbial pathogenesis. - Backert, Steffen; Feller, Stephan M.; Wessler, Silja (Trends in Biochemical Sciences, 2008)
Abl family kinases are central regulators of multiple cellular processes controlling actin dynamics, proliferation and differentiation. Recent studies indicate that different pathogens highjack Abl kinase signalling to reorganize the host actin cytoskeleton and promote the tyrosine phosphorylation of four known bacterial and viral effector proteins. Abl signalling is implicated in such diverse processes as microbial invasion, viral release from host cells, actin-based motility, actin-rich pedestal formation and cell scattering. Thus, Abl kinases are emerging as crucial regulators of multiple pathological signalling cascades during infection. Therapeutic intervention against Abl kinase activity might be an effective and novel strategy to combat serious microbial diseases.